(untitled) (Música Hodie, 2024)
The background of this study is rooted in the need to understand how folk music, as an integral part of cultural heritage, has adapted to rapid changes in educational paradigms influenced by technological advancement and globalization. Despite the impact of technological advances and global cultural integration on folk music education, few reviews have examined how technology and global perspectives are transforming folk music education and identified emerging pedagogical trends. This article provides a comprehensive review of the trends, technologies, and global perspectives shaping folk music education through a thematic review and analysis of 43 literature publications from 2013 to 2023. This study used ATLAS.ti 23 to assist in thematic analysis, and the analysis resulted in four themes: Cultural Music Diversity, Folk Music Curriculum, Global Perspective Education, and Technology Impact Education. Findings indicate that while folk music education has made significant advances in technology and global perspectives, challenges remain in balancing tradition and innovation. Implications for future pedagogy demonstrate the need for continued research to develop strategies that preserve the essence of folk music traditions while fostering adaptability to new educational contexts.